Effects of sorghum genotype on milling characteristics and growth performance of nursery pigs - Jones, C.L.; Hancock, Joe D.; Behnke, Keith C.; Sowder, C.M.; McKinney, Leland J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The sorghums used in our experiment (mill-run, red feed-quality, and white food-quality) had greater true grinding efficiency than corn. Mill-run sorghum also ground easier and with greater true efficiency than the red and food quality (white seed/tan plant) experimental sorghums. Diets with the red sorghum had greater pellet production rate and pellet durability index than diets with the food-quality sorghum. In a nursery pig growth assay, corn-based diets had greater digestibility of gross energy than the sorghum diets, and the white sorghum had greater digestibilities of dry matter, nitrogen, and gross energy than the red sorghum. However, ADG, ADFI, and G/F were not different among pigs fed the various cereal grains.
Keywords: Swine; Nursery pigs; Sorghum; Food quality